Asherman's Syndrome: it may not be all our fault. Issue 8 (25th July 2018) - Santamaria, Xavi; Isaacson, Keith; Simón, Carlos
Abstract: Asherman's Syndrome (AS) is an acquired condition defined by the presence of intrauterine adhesions (IUA) that cause symptoms such as menstrual abnormalities, pelvic pain, infertility, recurrent miscarriage, abnormal placentation and attendant psychological distress. Classically, AS is considered an iatrogenic disease triggered by trauma to the pregnant uterus. Different factors can cause the destruction of the endometrium, thus affecting the endometrial stem cell niche and creating IUAs. Curettage of the pregnant uterus appears to be the most common source of this destruction. Nevertheless, some AS cases have been associated with congenital uterine abnormalities and infections, and there are some idiopathic cases without any prior surgical procedures, suggesting a putative constitutional predisposition to IUA. Factors reported to cause AS share an underlying inflammatory mechanism leading to defective endometrial healing and vascularization. Interestingly, distinct genetic profiles have been observed in the endometrium of AS patients. These data suggest that AS might not just be an iatrogenic complication, but also the result of a genetic predisposition. Elucidating the possible physiopathological processes that contribute to AS will help to identify patients at risk for this condition, providing an opportunity for prevention.